Road user charging and how it could affect public transport provision in Great Britain - Graham,DJ (Public Transport International, 2006)
The effects of charging road users for reducing congestion on the public transport facilities in Great Britain are discussed. Impressive charges in road traffic volumes and speeds have been recorded within the zone since the introduction of the scheme on 17 February 2003. The congestion charging has resulted in a reduction of measures of congestion by 30% and a decrease in traffic entering during charging hours by 18%. The imposition of congestion charges incorporates congestion and environmental costs as well as the prevailing national rate of fuel tax. The road user charging for public transport operators frees up the capacity of the road network due to the reduction of traffic volumes. The introduction of road user charging shifts the balance in favor of high densities and strengthens the case for investment in urban transport.